GAGASAN RESTRUKTURISASI KEWENANGAN NOTARIS DALAM YURISDIKSI EKSTRATERITORIAL INDONESIA - Hatta Isnaini Wahyu Utomo (Lembaga Kajian Hukum, Fakultas Hukum, Universitas Singaperbangsa Karawang, 2019)
Increased opportunities for trade in goods and services in the global sphere in the era of the ASEAN Economic Community (MEA) must be responded with the ability of the state to provide legal protection for the people of Indonesia who are involved in the MEA free market. The notary is expected to be able to provide services not only at the regional level but also nationally and even globally. This gave birth to the idea of optimizing the role of the Notary. This study uses normative legal research methods conducted to find solutions to existing legal problems. The research approach used is the statute approach and the conceptual approach. The results of this study analyze the political, philosophical and sociological foundations in the notion of expanding the area of notary public office and the concept of globalization of the implementation of notary office duties in the extraterritorial jurisdiction.